1^2-2^2+3^2-4^2+5^2-6^2+...+2009^2-2010^2
Tính:\(^{1^2}\)
a) 1^2-2^2+3^2-4^2+5^2-6^2+....+2009^2-2010^2
b) 3^2010-(3^2009+3^2008+3^2007+...+3+3^0)
tính các dãy số sau:
-1-2+3+4-5-6+7+8-.....-2009-2010+2011
-1-2+3-4-5+6+....-2009+2010-2011
tinh tong
a)s=1+(-2)+3+(-4)+.......+2009+(-2010)
b)s=1+(-2)+(-3)+4+5+6(-6)+(-7)+......+2008+2009+(-2010)
1/2*2/3*3/4*4/5*5/6*.....*2009/2010
\(\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{3}{4}\cdot\frac{4}{5}\cdot....\cdot\frac{2009}{2010}\)
\(=\frac{\left(2\cdot3\cdot4\cdot5....\cdot2009\right)}{\left(2\cdot3\cdot4\cdot5\cdot....\cdot2009\right)\cdot2010}=\frac{1}{2010}\)
1/2x2/3x3/4x4/5x5/6x......x2009/2010
=(2x3x4x5x.....x2009)/(2x3x4x5x......x2009).2010=1/2010
Tính tổng:
a,S1=1+(-2)+3+(-4)+..........+2009+(-2010)
b,S2=1+(-2)+(-3)+4+5+(-6)+(-7)+............+2008+2009+(-2010)
a,S1=1+(-2)+3+(-4)+..........+2009+(-2010)
S1=-1.(2010:2)
S1=-1005
b,S2=1+(-2)+(-3)+4+5+(-6)+(-7)+............+2008+2009+(-2010)
S2=-1.(2010:2)
S2=-1.1005
S2=-1005
Tính
A=1-2+3+4-5-6+7+8-9-.....+2007+2008-2009-2010
B=2^2005-2^2003-2^2001-......-2-1
C=2+4+4+8+10-12-14+16+......-2006+2008+2010-2012
D=1-2-3-4+5-6-7-8+9-10-11-......-2010
Bài 1: Tính tổng
S = 1 - 2 + 3 - 4 + 5 - 6 + ... + 2009 - 2010
Bài 2: Tính tổng
P = 0 - 2 + 4 - 6 + ... + 2010 - 2012
1) tìm số tự nhiên x,biết rằng: 1/3+1/6+1/10+...+2/x(x+1)=2007/2009
2)so sánh:S=2/1*2*3+2/2*3*4+2/3*4*5+...+2/2009+2010+2011 và P=1/2
1.1/3+1/6+1/10+...+2/x.(x+1)=2007/2009
=>2/6+2/12+2/20+...+2/x.(x+1)=2007/2009
=>1/2-1/3+1/3-1/4+1/4-1/5+...+1/x-1/(x+1)=2007/2009:2
=>1/2-1/(x+1)=2007/4018
=>1/(x+1)=1/2-2007/4018
=>1/x+1=1/2009
=>x+1=2009
=>x=2009-2008
=>x=1
vậy x=1
làm đúng rồi nhưng phần:
x+1=2009
x=2009-1
x=2008
mà bạn
Đặt A= \(\frac{1}{3}+\frac{1}{6}+\frac{1}{10}+...+\frac{2}{x\times\left(x+1\right)}=\frac{2007}{2009}\)
\(\Rightarrow\) \(\frac{1}{2}A=\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+...+\frac{1}{x\times\left(x+1\right)}=\frac{2007}{4018}\)
\(\Leftrightarrow\frac{1}{2}A=\frac{1}{2\times3}+\frac{1}{3\times4}+\frac{1}{4\times5}+...+\frac{1}{x\times\left(x+1\right)}=\frac{2007}{4018}\)
\(\Leftrightarrow\frac{1}{2}A=\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+...+\frac{1}{x}-\frac{1}{x+1}=\frac{2007}{4018}\)
\(\Leftrightarrow\frac{1}{2}A=\frac{1}{2}-\frac{1}{x+1}=\frac{2007}{4018}\)
\(\Rightarrow A=1-\frac{2}{x+1}=\frac{2007}{2009}\)
\(\Rightarrow\frac{2}{x+1}=1-\frac{2007}{2009}\)
\(\Leftrightarrow\frac{2}{x+1}=\frac{2}{2009}\)
\(\Rightarrow x+1=2009\)
\(\Leftrightarrow x=2009-1\)
\(\Leftrightarrow x=2008\)
Vậy x=2008
Cho A = 1/2001+2/2009+3/2008+........2009/+ 2010/1, B = 1+1/2+1/3+1/4+1/5+1/6+.......1/2010+1/2011. Tính A/B